PENGUATAN CITRA PEKALONGAN SEBAGAI KOTA BATIK MELALUI PEMBANGUNAN PUSAT INFORMASI UMKM BATIK BERBASIS MOBILE YANG MAMPU MENINGKATKAN DAYA SAING UMKM BATIK DALAM MENGHADAPI PERSAINGAN ERA MASYARAKAT EKONOMI ASEAN - Christianto, Paminto Agung; Susanto, Eko Budi; Kurniawan, M. Faizal (JURNAL LITBANG KOTA PEKALONGAN, 2016)
ASEAN ECONOMIC COMMUNITY (AEC) HAS STARTED, THIS WOULD OPEN UP MANY OPPORTUNITIES OR EVEN POSE A THREAT TO HUNDREDS OF SMES BATIK PEKALONGAN. OPPORTUNITIES OBTAINED IS THE EXPANSION OF MARKET SHARE, WHEREAS THE EXISTING THREAT IS THE COLLAPSE OF SMES BATIK PEKALONGAN BECAUSE OF COMPETITION WITH SIMILAR EFFORTS FROM COUNTRIES BELONGING TO THE MEA, WHICH WOULD POTENTIALLY INCREASE IN UNEMPLOYMENT, POVERTY AND CRIME RATE IN PEKALONGAN. THIS STUDY INTENDS TO ESTABLISH AN INFORMATION CENTER PEKALONGAN BATIK SMES CAPABLE OF INTEGRATING MOBILE-BASED SMES WITH BATIK PEKALONGAN BATIK OBSERVERS, AMONG FINANCIAL INSTITUTIONS, ACADEMIA, THE CHAMBER OF COMMERCE AND THE CITY OF PEKALONGAN. THIS RESEARCH RESULT IS THE CREATION OF A PROTOTYPE THAT HAS BEEN DEVELOPED WITH A WIDER RANGE OF TERRITORY NOT ONLY IN PEKALONGAN, BUT TO THE AREA OF CENTRAL JAVA. WITH THE INFORMATION CENTER, THEN BATIK SMES WILL HAVE THE ADVANTAGE IN COMPETING IN THE ERA OF THE ASEAN ECONOMIC COMMUNITY (AEC), THROUGH THE ACCELERATION OF INFORMATION THAT CAN BE RECEIVED, EITHER IN THE FORM OF INFORMATION FINANCING FROM FINANCIAL INSTITUTIONS, INFORMATION BUSINESS OPPORTUNITIES OF THE CHAMBER OF COMMERCE OF PEKALONGAN, INFORMATION INNOVATION FROM ACADEMICS AND BATIK OBSERVERS, AS WELL AS INFORMATION PROGRAMS RELATED TO HUMAN RESOURCE DEVELOPMENT OF THE BATIK SMES OF THE GOVERNMENT OF CENTRAL JAVA